2023
DOI: 10.1038/s41392-023-01552-y
|View full text |Cite
|
Sign up to set email alerts
|

A metabolome atlas of mouse brain on the global metabolic signature dynamics following short-term fasting

Yaping Shao,
Zhenfa Fu,
Yanfeng Wang
et al.

Abstract: Calorie restriction (CR) or a fasting regimen is considered one of the most potent non-pharmacological interventions to prevent chronic metabolic disorders, ameliorate autoimmune diseases, and attenuate aging. Despite efforts, the mechanisms by which CR improves health, particularly brain health, are still not fully understood. Metabolic homeostasis is vital for brain function, and a detailed metabolome atlas of the brain is essential for understanding the networks connecting different brain regions. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Branched-chain amino acids, a crucial raw material for the synthesis of Glu and GABA, also gained an increase after fasting. 23…”
Section: Discussionmentioning
confidence: 99%
“…Branched-chain amino acids, a crucial raw material for the synthesis of Glu and GABA, also gained an increase after fasting. 23…”
Section: Discussionmentioning
confidence: 99%
“…The recent study, published in Signal Transduction and Targeted Therapy by Le's team (Shao et al, 2023 ), provides a comprehensive and detailed metabolome atlas of the mouse brain based on the global metabolic signature dynamics across multiple brain regions in response to short-term fasting (STF) (Shao et al, 2023 ). This research revealed significant region-specific metabolic remodeling involving lipids, saccharides, and amino acid neurotransmitters under food deprivation ( Figure 1 ) (Shao et al, 2023 ). These discoveries furnish a crucial molecular foundation and novel insights into the mechanisms through which STF improves brain health.…”
Section: Introductionmentioning
confidence: 99%
“… Metabolomic analysis of seven brain regions in C57BL/6 mice under fasting conditions (3 h, 6 h, 12 h, and 24 h) and ad libitum feeding. A heat map was presented to illustrate the differential expression of metabolites in these seven brain regions (Shao et al, 2023 ). The analysis revealed that short-term fasting induced a global lipid and amino acid metabolism remodeling, mainly targeting FAs, BCAAs, Glu, GABA, and the citrulline–NO cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations